A Comparative Study of ECG and Blood Pressure among Smokers and Non-Smokers - Kanwal Abbas Bhatti, Noor Nabi Siyal, Altaf Hussain Memon, Ghulam Muhammad Phull, Hanozia Hassan, Mukhtiar Ahmed Abro (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Smoking is one of the most significant risk factors for a wide range of illnesses, including lung and heart disease, cancer, and many others. There are currently 1.2 billion smokers around the globe, and that figure is expected to climb by 1.6 billion by the year 2020. Tobacco use kills about 3.5 to 4 million people worldwide every year, and this number is expected to rise to 10 million by 2020. Mostly, the acute consequences of smoking are well-documented. These contain an increase in heart rate and blood pressure, as well as a decrease in cardiac output and vasoconstriction. Smoking is the subject of the current investigation. Smokers vs non-smokers on ECG and blood pressure. Objectives: To examine the differences in blood pressure between people who smoke and those who don’t and to examine the differences in ECG waveforms between smokers and nonsmokers Methods: May 2020 through April 2021 was when the research was carried out at PUMHS, There were fifty smokers and fifty non-smokers aged 20 to 35 years old in each group. After a thorough description of the study’s goals and objectives, only those individuals who agreed to take part were included. Participants who met certain criteria were discarded. Blood pressure (sitting position) and an electrocardiogram (supine posture) were got while the individuals were in a resting condition. Results: The research had 100 participants, 50 of them were smokers and the other 50 were non-smokers. Nonsmokers and smokers had similar age distributions, and the disparity was not statistically significant (p-value- 0.97). In Lead III, 54% had an inverted wave compared to 40% normal and this difference found to be statistically significant, i.e. highest percentage of flat and inverted waves found in smokers. The difference in presence of abnormal waves among smokers and non-smokers in Lead V1 to V4 was found to be statistically significant. When a comparison of vitals and ECG between smokers based on pack-years (1- 3 pack-year, 4-6pack year, and 7-9pack year) was done there was no statistical significance attributed to various other parameters like pulse, heart rate, respiratory rate, systolic BP, diastolic BP, P wave amplitude, P wave duration, PR interval, QRS duration, QT interval, and QRS axis, except QTc. Conclusion: Researchers found that in smokers, there were a variety of ECG alterations and an increase in blood pressure despite the lack of any heart disease.